Performance analysis of 802.11n-based cognitive wireless system with joint rate and power adaptation. Issue 11 (1st November 2020) - Itraj, Santosh; Bombale, Uttam; Patil, Pravinkumar; Patil, Meenakshi
ABSTRACT: Cognitive radio technology is a solution to the spectrum scarcity problem that exists in today's wireless networks. It provides spectrum conscious paradigm. However, these wireless systems impose eccentric challenges because of dynamic spectrum availability and diverse quality of service requirements. This paper investigates the performance of the adaptive cognitive system in multi-user and multi-channel environment. Since the system has to work in such a hostile environment, to enhance the performance of the system, modified joint rate and power adaptation algorithm is proposed. The novel packet-based water-filling power adaptation (PBWFPA) algorithm proposed in this treatise defines power per packet. The channel environment is consisting of multi-path fading channels TGn-A (Throughput task group-A) and TGn-D (Throughput task group-D). The adaptation algorithm considers interweave scheme in the performance evaluation of the cognitive system. The transmitter adapts transmit parameters based on channel state information (CSI) and soft information regarding activities of the primary users in the cognitive environment. The transmit parameters are computed at the receiver end and fed to the transmitter through the feedback channel. The simulation results reflect significant improvement in the throughput of the system even in an opportunistic channel-sharing environment. Higher-quality channel selection ensures the enhancement in the throughput of the system.